Characteristics, clinical outcomes, and risk factors of SARS-COV-2 infection in adult acute myeloid leukemia patients: experience of the PETHEMA group. Issue 12 (15th October 2021) - Palanques-Pastor, Tomás; Megías-Vericat, Juan Eduardo; Martínez, Pilar; López Lorenzo, José Luis; Cornago Navascués, Javier; Rodriguez Macias, Gabriela; Cano, Isabel; Arnan Sangerman, Montserrat; Vidriales Vicente, María Belén; Algarra Algarra, Jesús Lorenzo; Foncillas, María Ángeles; Herrera, Pilar; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection produces higher morbidity and mortality in hematological malignancies, but evidence in acute myeloid leukemia (AML) is scarce. A multicenter observational study was conducted to determine the clinical outcomes and assess the impact of therapeutic approaches in adult AML patients with SARS-CoV-2 infection in the first wave (March–May 2020). Overall, 108 patients were included: 51.9% with active leukemia and 70.4% under therapeutic schedules for AML. Signs and symptoms of SARS-CoV-2 were present in 96.3% of patients and 82.4% received specific treatment for SARS-CoV-2. The mortality rate was 43.5% and was correlated with age, gender, active leukemia, dyspnea, severe SARS-CoV-2, intensive care measures, neutrophil count, and D-dimer levels. A protective effect was found with azithromycin, lopinavir/ritonavir, and normal liver enzyme levels. During the SARS-CoV-2 first wave, our findings suggested an increased mortality in AML in a short period. SARS-CoV-2 management could be guided by risk factors in AML patients.